Phytotoxic, Cytotoxic and Insecticidal Activities of Chrysophthalmum dichotomum Boiss. and Heldr. - Ayaz, Fatma; Kucukboyaci, Nurgun; Bani, Baris; Sener, Bilge; Choudhary, Muhammad Iqbal (Manuscript Technomedia LLP, 2018)
Background: Chrysophthalmum dichotomum Boiss. and Heldr. (Asteraceae) is an endemic herbaceous plant to Southern part of Turkey. Aim: To investigate in vitro phytotoxic, cytotoxic and insecticidal activities of C. dichotomum. Methods: The MeOH extract of C. dichotomum was fractionated through subsequent solvent extractions in increasing polarity with n-hexane, chloroform and n-butanol. The MeOH extract and its fractions were evaluated for their biological acitivities using in vitro screening bioassays such as cytotoxicity on brine shrimps, phytotoxicity against Lemna minor and insecticidal activity against Rhyzopertha dominica and Tribolium castaneum. Results: The n-hexane and chloroform fractions showed significant phytotoxic activity (100 % growth inhibition) at 1000 mu g/ml against L. minor. The brine shrimp lethality test revealed that the chloroform and remaining water fractions of C. dichotomum have moderate and positive lethality with LD50 values of 169.48 and 46.26 mu g/mL, respectively. In addition, the chloroform and n-butanol fractions had low and moderate insecticidal activity with 20 and 40 % of mortality against Tribolium castaneum, respectively. Conclusion: This study demonstrates that C. dichotomum consists of bioactive constituents responsible for phytotoxicity, cytotoxicity on brine shrimps and insecticidal activity.
Keywords: Chrysophthalmum dichotomum; Phytotoxicity against Lemna minor; Cytotoxicity on brine shrimps; Asteraceae; Insecticidal activity